CATCH RESULTS PER EFFORT (CPUE) AND MAXIMUM SUSTAINABILITY YIELD (MSY) ANALIZYS OF SELAR FISH (SELAROIDES SPP.) AT THE DONGGALA REGENCY WATERS - Oktafiati, Nur Afni; Juliani, Juliani; Irawan, Aditya; Pagoray, Henny; Sukarti, Komsanah; Fitriyana, Fitriyana (Jurnal Perikanan Unram, 2025)
The potential of Selar Fish (Selaroides spp.) caught by fishermen in the waters of Donggala Regency requires in-depth study to support sustainable management and ensure its sustainability in the future. This research aims to analyze catch per unit effort (CPUE) as well as the maximum sustainable potential of trevally (Selaroides spp.) in the region. The research location covers three administrative areas, namely Labean Village (Balaesang District), Ogoamas Village (North Sojol District), and Labuan Bajo Village (Banawa District). The research results show that the average trevally production during the 2017-2023 period reached 5,019.06 tons per year, with an average fishing effort of 2,479.66 trips per year. The average catch per attempt (CPUE) was recorded at 2,394.92 tons/trip. Based on analysis using the Schaefer model, the maximum sustainable potential (hMSY) is obtained with a maximum biological production of 6,238 tons per year. Maximum economic profit is achieved at a hMEY production level of 6,152 tons per year, while the equilibrium condition for fisheries in open access (hOAY) occurs at a production level of 2,579 tons per year. In terms of fishing effort, the biologically optimum number of efforts (EMSY) is 3,175 trips per year, economically (EMEY) it is 2,803 trips per year, while in open access conditions (EOAY) it reaches 5,606 trips per year. This data indicates that MEY-based management is more advisable to maximize economic benefits while maintaining the sustainability of trevally resources. These findings can be a basis for policy makers in establishing sustainable fisheries management strategies in the waters of Donggala Regency